Global Mobility beyond Traditional Assignments - A Review on Flexpatriates and International Business Travellers - Jayasekara, Padmini (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this paper is to explore the concept of flexpatriates and international business travellers (FIBT) and related issues of FIBTs. Finally, the outcome of the paper is enriched by presenting a policy oriented conceptual model for managerial concern to resolve such issues of FIBSs. A literature-based data compilation was done to develop this model. The model mainly outlines the necessity of giving strategic policy orientation on managing FIBTs by considering several supportive channels: organizational support and social support for both assignees and families.